Key cultural texts in translation - Malmkjær, Kirsten; Serban, Adriana; Louwagie, Fransiska (Benjamins translation library ;, 2018)
In the context of increased movement across borders, this book examines how key cultural texts and concepts are transferred between nations and languages as well as across different media. The texts examined in this book are considered fundamental to their source culture and can also take on a particular relevance to other (target) cultures. The chapters investigate cultural transfers and differences realised through translation and reflect critically upon the implications of these with regard to matters of cultural identity. The book offers an important contribution to cultural approaches in translation studies, with ramifications across different disciplines, including literary studies, history, philosophy, and gender studies. The chapters offer a range of cultural and methodological frameworks and are written by scholars from a variety of language and cultural backgrounds, Western and Eastern.